Skill Of Cadre In Determining Plotting Point On Growth Chart According To Characteristics, Source Information And Knowledge Of Cadre - Titus Priyo Harjatmo; Agni Nur Imanti (Politeknik Kesehatan Kemenkes Jakarta II, 2017)
Children are the next generation for a nation. Therefore a child must be prepared early on both mentally, socially and spiritually. Expected of the growth and Development can be optimal. To obtain optimal growth and development of the role of nutrition is very decisive. Posyandu is defined as a basic health activity organized from, by and for communities assisted by health workers. One of the Posyandu activities is to monitor the growth of children under five with KMS tools. If a Posyandu cadre has not understood the tendency of growth chart of KMS ,it will have an impact on the result of growth status of the child. The study conducted at one posyandu in Ciracas in East Jakarta on 33 Posyandu cadres showed that most of the cadres were unskilled in plotting the growth chart by 60.6% and the skilled 39.4%. Most cadres have female sex (97.0%), age of cadre most age 46-65 year that is 17 cadre (51.3%), long become cadre most 6-10 year 19 cadre (57.6%). While the highest level of cadre education is the basic education cadres of 15 cadres (44.1%), who have attended training on KMS only 16 cadres (48.5%), knowledge of cadres is mostly medium knowledge of 15 cadres (45.5%). From the results of the analysis shows that cadre skills depend on cadre knowledge. Suggestions for improving skills are the necessity of holding the rotating duties so that each cadre is skilled in carrying out the growth measurement path. For Puskesmas, it is necessary to hold regular training or refresher about Posyandu activity especially KMS plotting.